2011
DOI: 10.1002/cncr.26632
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Sexual Adjustment and Body Image Scale in women with gynecologic cancer

Abstract: BACKGROUND: There is evidence that treatment of gynecologic cancer (GC) negatively affects body image and sexuality. The Sexual Adjustment and Body Image Scale (SABIS-G) was developed to assess disturbances after diagnosis of GC. The objective of this study was to confirm the factor structure using a confirmatory factor analysis (CFA). METHODS: Women with a history of GC completed the SABIS-G, a 9-item self-report measure. Ninety randomly selected participants were used for the exploratory factor analysis (EFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Ferguson et al also found that the scale had an RMESA of 0.08. This showed that the adapted version of the scale had a good fit (Ferguson et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ferguson et al also found that the scale had an RMESA of 0.08. This showed that the adapted version of the scale had a good fit (Ferguson et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Ferguson et al. () found in their study on women with gynecological cancers that Cronbach's alpha coefficient was 0.91 for sexual adjustment and 0.88 for body image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…more recently, the sexual adjustment and Body image scale (saBis) for patients with breast cancer and the saBis-G for patients with gynecologic malignancies have been developed as tools to identify patients who are "significantly distressed" by problems with sexual function and/or sexual well-being. 18,19 these scales have been used to develop internet-based online support and sex therapy for patients in distress and have been shown to be feasible and effective in both female and male patients. 20,21 Ball et al 22 have performed a qualitative study of 13 male patients 6 years following treatment for rectal cancer and have found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the variation in the structure of necks among Chinese young males, neck classification was first conducted before the 3D model (Alexander, 1994;Brown, Cash, & Mikulka, 1990;Ferguson et al, 2012 andJiang, Zhang, Xia, &Hou, 2008). In this study, a factor analysis with varimax rotation was conducted on the 11 measurement parameters.…”
Section: Methodsmentioning
confidence: 99%